(untitled) (Faridpur Medical College Journal, 2016)
Hepatitis B Virus (HBV) infection can causes spectrum of diseases ranging from clinically asymptomatic state to the development of cirrhosis and hepatocellular carcinoma (HCC). There is ongoing debate in the management of asymptomatic patients with chronic hepatitis B virus (CHBV) infection with high DNA and normal ALT level. It has been recently shown that a significant proportion of patients with CHBV infection with high DNA and normal ALT level have significant histological abnormality. So this study was aimed to see the histological changes in patients with CHBV infection with high DNA and ALT level <2 times of upper limit of normal (ULN). Total 64 patients were included in this cross sectional study. Mean age was 29 years, 55 (85.9%) patients were men. Forty patients (62.5%) were HBeAg positive. Thirty seven (57.8%) patients had normal ALT levels and 27 patients (42.2%) had ALT levels 1-2 x ULN. Out of 64 patients 46.8% had significant histological abnormalities. Among them 31.2% had significant fibrosis and 26.5% had significant necroinflammatory changes. Among 37 patients with normal ALT levels 35% had significant histological abnormalities. But among 27 patients with ALT levels of 1-2 x ULN, 63% had significant histological abnormalities. In this series significant histological abnormalities were found in 40% of HBeAg+ve cases and 58.3% of HBeAg-ve cases. But this difference was not statistically significant. It was also found that patients with significant histological abnormalities were significantly older and had a lower median HBV DNA level, lower mean platelet count, lower mean prothrombin activity ratio and lower mean albumin level than patients with nonsignificant histological changes. In logistic regression analysis it was found that serum ALT levels and age at which patients entered the study were independently associated with the risk for significant histological abnormalities. Faridpur Med. Coll. J. Jan 2015;10(1): 3-8